Identification of Statistical Relations between Tax Policies in Voivodship Capitals and Local Housing Market Development - Zapotoczna, Marcelina; Cymerman, Joanna (Regional Barometer. Analyses & Prognoses, 2016)
The authors seek the correlations between local council policies concerning residential property taxation and the growth of local housing markets in voivodship capitals in 2007–2013. The first part of the paper contains the analysis of the dynamics of changes in local property taxes followed by the evaluation of the development levels of local housing markets and their linear ordering by means of the property market development indicator. Then, in order to capture the similarities and identify trends on the local housing markets, the cities were classified into homogenous clusters. In the last stage of the analysis the authors evaluated the relevance of property tax rates adopted locally on the growth of local housing markets. The study results showed no statistically relevant correlation between the analysed phenomena — i.e., no effect of the local property tax rates on the decisions made by investors on the local housing markets.